The electrical, dielectric and magnetic effect of strontium-substituted spinel ferrites for high-frequency applications - Salma Aman (Taylor & Francis Group, 2021)
Strontium-substituted spinel ferrites were prepared using the sol–gel method. The sample’s chemical formula was Cu1–xSrxFe2O4 (0.00, 0.20, 0.40, 0.60, 0.80 and 1.00). A cubic structure was discovered through X-ray diffraction (XRD) analysis. The lattice, constant, X-ray density and other structural parameters were increased with the substitution of strontium ion due to its larger ionic radius as compared with the ionic radius of manganese. It was discovered that the addition of strontium ions increased both activation energy and dc resistivity, whilst the decrease in resistivity with increasing temperature proved the semiconducting nature of samples. There was an abysmal disparity between the coerciveness and magnetization values. The permittivity was decreased with the addition of strontium ions. The low perittivity and high specific resistance suggested that prepared samples are suitable for high-frequency applications.